2011
DOI: 10.2214/ajr.10.4468
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatosis Intestinalis and Pneumoperitoneum After Bilateral Lung Transplantation in Adults

Abstract: Bilateral lung transplant recipients may develop benign PI or pneumoperitoneum after surgery. Benign PI in bilateral lung transplant recipients has a similar and specific linear and cystic appearance and is not due to ischemic bowel. No specific cause for the PI and pneumoperitoneum could be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 17 publications
3
37
0
Order By: Relevance
“…Although there have been rare case reports of PI developing in patients after thoracic organ transplant, 2,5 there is only one series published, which consisted of 7 patients presenting with pneumoperitoneum or PI after lung transplant. 13 The clinical presentation, radiographic appearance, and outcomes of previous case reports were quite similar to those for our 10 patients with PI. To our knowledge, this is the largest case series (consisting of 10 patients) of patients presenting with PI after lung transplant.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although there have been rare case reports of PI developing in patients after thoracic organ transplant, 2,5 there is only one series published, which consisted of 7 patients presenting with pneumoperitoneum or PI after lung transplant. 13 The clinical presentation, radiographic appearance, and outcomes of previous case reports were quite similar to those for our 10 patients with PI. To our knowledge, this is the largest case series (consisting of 10 patients) of patients presenting with PI after lung transplant.…”
Section: Discussionsupporting
confidence: 84%
“…This agrees with an earlier case series in which all cases were noted to involve the large bowel. 13 We found that 50% of our patients had PI associated with air under the diaphragm (pneumoperitoneum). Presence of pneumoperitoneum with PI was not associated with poor outcomes (1 death was due to late lung infection), and only 1 patient required surgical exploration with documented bowel ischemia.…”
Section: Discussionmentioning
confidence: 59%
“…1,7,8 In lung transplant patients, there have been several reports on pneumatosis intestinalis and pneumoperitoneum without evidence of an organ perforation. 2,4,6 As for the cause, Khalil and others have proposed different theories. 1,5 Increased intraintestinal or intramediastinal pressure due to either bowel or pulmonary obstruction can be responsible for dissection of gas into the bowel wall in the scope of a "mechanical theory."…”
Section: Discussionmentioning
confidence: 99%
“…In addition to medication-induced pneumatosis, systemic diseases (eg, lupus or acquired immunodeficiency syndrome), inflammatory bowel diseases, and pulmonary diseases (eg, asthma or cystic fibrosis), as well as bone marrow transplant, abdominal, and thoracic organ transplant, can lead to pneumatosis intestinalis. [1][2][3][4][5][6][7] In this case report, we present a patient with recurrent pneumoperitoneum and pneumatosis intestinalis after bilateral lung transplant in which we used a conservative approach involving antibiotic therapy with metronidazole.…”
Section: Introductionmentioning
confidence: 99%
“…There are two popular postulated mechanisms of benign PI: mechanical and bacterial. The mechanical theory posits increased positive pressure and consequent leakage of air through microscopic breaks in the bowel wall 1 2 11 13. The bacterial theory puts forth translocation of gas-producing bacteria among the normal gut flora into the bowel wall and gas production within the mucosal layers 2 11…”
Section: Discussionmentioning
confidence: 99%